The Impact Of Balance Funds And Local Real Income On Poverty In Papua Province - Sutrisno Sutrisno; Fahrizal Taufiqqurrachman (Universitas Bangka Belitung, 2025)
The purpose of this study is to examine how poverty rates in Papua Province are impacted by Local Original Revenue (LOR) and balancing funds, such as the General Revenue Sharing (GRS) and the Specific Allocation Grant (SAG). Multiple regression analysis is the research tool employed in this study, enabling researchers to assess the correlation between various variables. Regional financial statistics and poverty indicators for the years 2011–2023 are among the data used. The study's findings demonstrate that LOR and the balance fund significantly and favorably lower Papua's poverty rate. This study concludes that increased fund allocation from the central government and better management of LOR can contribute to improving community welfare. Therefore, it is recommended that local governments increase their financial management capacity and prioritize programs that can effectively reduce poverty.